Fibrin D-dimer, Tissue Plasminogen Activator, Plasminogen Activator Inhibitor, and the Risk of Major Ischaemic Heart Disease in the Caerphilly Study - Lowe, G. D. O.; Yarnell, J. W. G.; Sweetnam, P. M.; Rumley, A.; Thomas, H. F.; Elwood, P. C. (Thrombosis and Haemostasis, 1998)
Plasma levels of fibrin D-dimer, tissue plasminogen activator (tPA) and plasminogen activator inhibitor (PAI) have been associated with ischaemic heart disease (IHD). However their associations with incident IHD in samples of the general population are not established. D-dimer antigen, tPA antigen and PAI activity were measured in stored, fasting plasma samples from 1,998 men aged 45-65 examined between 1984 and 1988, during the first re-examination of the Caerphilly Study cohort. These variables were related to major IHD events (myocardial infarction or IHD death) which occurred in 129 men during a follow-up period which averaged 61 months. Mean fibrin D-dimer was higher in men who developed IHD events (90 vs. 71 ng/ml; age-adjusted logarithmic mean difference 0.21; 95% CI 0.11, 0.30; p <0.0001). This association remained after adjusting for baseline IHD and for other risk factors including fibrinogen: the adjusted relative odds of IHD in the highest fifth of D-dimer were 3.5 (95% CI 1.8, 6.9; p = 0.0003). Mean tPA antigen was also higher in men who developed IHD (12.6 vs. 11.6 ng/ml; mean difference 0.9; 95% CI 0.2, 1.7; p = 0.02); however this difference largely disappeared after adjusting for other risk factors. PAI activity was not associated with risk of IHD.